Toxoplasmosis: A Review - Sadiya A. Anah (Journal of Global Pharma Technology, 2016)
Toxoplasmosis one of the common human-animal diseases (Zoonotic diseases) caused by a parasite belongs to the group of coccidian, class of sporozoa known as the Toxoplasma gondii, an intracellular obligate parasite, especially in nucleic cells, as noted inside the nucleus.Keywords: Human-animal diseases; Zoonotic diseases; Parasite; Tissues.